Growing like Germany: Local public debt, local banks, low private investment - Mathias Hoffmann; Iryna Stewen; Michael Stiefel (Bank of Finland, 2022)
Over 2010-2016, municipal debt in Germany crowded out private investment worth 1 percent of GDP. Forced to lend to municipalities by their statutes, local public banks compensated for declining municipal-debt yields by charging higher rates to firms in Germany's locally segmented credit markets. The ensuing crowding-out was made worse by increased municipal borrowing when expensive fiscal commitments were shifted from federal and state to the municipal levels following the introduction of the debt brake. Our results identify new channels through which low interest rates adversely affect real outcomes and locally segmented credit markets can amplify contractionary effects from fiscal austerity.
urn:nbn:fi:bof-202208221344
Keywords: E22; E40; E62; G21; G28 F21; F32; H32; 330; local public finance; firm-level investment; crowding-out; fiscal austerity; global and intraEuropean imbalances